Perlindungan Hukum terhadap Debitur yang Wanprestasi terhadap Penarikan Objek Kredit Tanpa Persetujuan Debitur - Leode, Roosdiana Marthina; Moonti, Roy Marthen; Ahmad, Ibrahim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of financing practices with fiduciary guarantees in Indonesia often raises legal issues, especially regarding the unilateral withdrawal of credit objects by creditors against defaulting debtors. This action is often carried out without the consent of the debtor or a court decision, thus potentially violating the principles of justice and the principle of due process of law. This research aims to analyze the form of legal protection for debtors in a fiduciary financing agreement. The type of research used is normative juridical with an approach to legislation and court decisions. The results showed that the act of unilateral withdrawal can be categorized as a civil and criminal tort. Therefore, regulatory reform, increased legal literacy, and a fair and humanist dispute resolution mechanism are needed. It is recommended that fiduciary execution be carried out in accordance with legal procedures to protect the debtor's constitutional rights and ensure fairness in contractual relationships.